Elections and Local Government Performance in Brazil - Cavalcante, Pedro Luiz Costa (Organizações & Sociedade, 2017)
The 1988 federal constitution introduced a complex and innovative institutional arrangement that not only reestablished political rights and democratic procedures, but also reinforced decentralization as a fundamental guideline to policy implementation in Brazil. As a result, municipalities have become pivotal actors in the policymaking process. Scholars of Latin American politics have given much emphasis on the causes and determinants of decentralization, but not much has been done toward understanding how this increased decentralization has affected policymakers behavior and policy outcomes, more generally. This paper aims to do exactly that. Specifically, it investigates how institutional arrangements and electoral competition affect local government performance. The theoretical basis is the electoral democratic theory that broadly highlights elections as instruments of citizen’s control in retrospective and prospective voting approaches. The research employs a large-N cross-sub national analysis based on a dataset of electoral, partisan, socioeconomic and public financial information collected of Brazil’s 5500 municipalities. Local government performances, our dependent variables, are synthetic indicators created from 2009 national wide surveys of public education, health, housing and welfare services. The OLS regression results confirm the hypothesis that politics variables do matter on how politicians make decisions and implement policy under the new Brazilian democratic Era. The empirical evidences suggest that although electoral competition does not present direct effect on government performance, ideology and citizens’ participation do. Therefore, this paper helps to expand our understanding of political system impact on policy outputs, which is extremely important not only to academic purpose but also as decision support for policymakers.